Forjar Constitución: México 1916-17 - Knight, Alan (Anuario de Historia de América Latina, 2017)
This chapter discusses the creation and character of the Mexican Constitution of 1917. It describes the political, economic and social context in which the Constitution emerged; explains the motivation of the Carrancista regime in creating it; and traces the process – rapid and rushed – whereby the Constituent Congress was elected. It then analyses the make-up of the Congress, in terms of social class, occupation, age and ideological affiliation; and offers a resumé of the congressional debates – the chief concerns, the notable omissions, and the historico-philosophical allusions. Finally, it offers some general observations regarding the principal ideological currents – liberal, jacobin and social-reformist – that swirled within the Congress, thus suggesting how, in the years after 1917, the new Constitution could serve, in flexible fashion, to legitimise a variety of policies, depending on the demands and pressures of changing circumstances.
Keywords: Mexico; Mexican Revolution; Mexican Constitution of 1917; Venustiano Carranza; Liberalism; Jacobinism